Investigation of Geometrical and Microstructural Influences on the Mechanical Properties of an Extruded AA7020 Tube - Reblitz, Jonas; Wiesenmayer, Sebastian; Trân, Ricardo; Merklein, Marion (Production at the Leading Edge of Technology, 2023)
In the automotive sector, an important strategy for reducing CO2-emissions is lightweight construction. In this regard, body-in-white parts offer a high potential for weight reductions by substituting conventional steel parts with tubular, aluminum-based components. Due to their high strength-to-weight-ratio and high crashworthiness, tube profiles are often used as safety-relevant car body components. Therefore, an exact determination of the material properties is necessary, in order to achieve a high prediction accuracy of FE-simulations. In contrast to the testing of flat semi-finished parts, there are only few standardized methods for the material characterization of tubular components. Furthermore, a profound knowledge regarding the influences of geometry and manufacturing process of the tube profiles on the material properties has to be gained. Thus, AA7020 tubes are analyzed in this research work. Tensile specimens are cut out of a tube by a laser-cutting machine. As a result, the cross-section of the samples is curved as well. To ensure a proper material testing, the clamping jaws for the tensile test are adjusted to the curvature of the samples. For the characterization of the tube properties, caused by the manufacturing process, optical measurements are performed. The mechanical properties of the different grain structures are determined by the thermo-mechanical simulator Gleeble 3500 in T6 condition. Therefore, tensile specimens with a reduced wall thickness are prepared. Afterwards the curved tensile samples are tested in T6 and W-temper condition. To validate the comparability of the determined material properties, a comparison is conducted with flat specimens prepared from the semi-finished tube profiles.<br
Keywords: Material characterization; W-temper condition; Tubes